Sequential testing with Xpert MTB/RIF assay for diagnosis of tuberculous meningitis in Maharaj Nakorn Chiang Mai University Hospital - Poramed Winichakoon; Kanokwan Watcharasaksilp; Sunisa Butphet; Kanlaya Wongworapat; Chansom Pantip; Phadungkiat Khamnoi; Khuanchai Supparatpinyo; Parichat Salee (Scientific Reports)
Abstract Early diagnosis and appropriate treatment are essential for reducing morbidity and mortality in tuberculous meningitis (TBM). This study aimed to evaluate the diagnostic performance of the Xpert MTB/RIF assay for the diagnosis of TBM in patients with subacute lymphocytic meningitis. This cross-sectional study included 65 cerebrospinal fluid (CSF) specimens from patients at Maharaj Nakorn Chiang Mai University Hospital, Thailand, between January 2015 and March 2016. Mycobacteria growth indicator tube (MGIT) culture was used as the reference standard. Sensitivity, specificity, and agreement between Xpert MTB/RIF and MGIT culture were calculated. Sequential testing using a TBM score, followed by Xpert MTB/RIF was also analyzed. Xpert MTB/RIF demonstrated 83.33% sensitivity (95% CI 57.19–98.22) and 96.23% specificity (95% CI 87.02–99.54). Agreement between Xpert MTB/RIF and MGIT culture was 93.85% (p < 0.001), with a kappa score of 0.80 (95% CI 0.60–0.99). Sequential testing with a TBM score cut-off of 6, followed by Xpert MTB/RIF improved specificity from 96.23 to 97.15%. The Xpert MTB/RIF assay is a rapid and valuable tool for detecting Mycobacterium tuberculosis in centrifuged CSF specimens. A diagnostic algorithm incorporating the TBM score enhances performance, balancing sensitivity and specificity, and could improve patient outcomes in resource-limited settings.